European criminal law / Kai Ambos. - Ambos, Kai, 1965- (Cambridge University Press, 2018)
Since their creation, the European Union and the Council of Europe have worked to harmonise the justice systems of their member states. This project has been met with a series of challenges. European Criminal Law offers a compelling insight into the development and functions of European criminal law. It tracks the historical development of European criminal law, offering a detailed critical analysis of the criminal justice systems responsible for its implementation. While the rapid expansion and transnationalisation of criminal law is a necessary response to the growing numbers of free movement of persons and goods, it has serious implications for the rights of European citizens and needs to be balanced with rights protections. With its close analysis of secondary legislation and reliance on a wide variety of original sources, this book provides a thorough understanding of European Criminal Law and the institutions involved.